Responsive Justice in China During Transitional Times: Revisiting the Juggling Path Between Adjudicatory and Mediatory Justice - Gu Weixia (Washington University Global Studies Law Review, 2015)
China has been discussed in international literature as a transitional state in both social and economic senses; however, scholarly literature analyzing how China’s justice system responds to the country’s social and economic transitions is scant. This Article studies the international “transitional justice” framework that examines justice systems in economic, societal, and political transition in post-Communism Central and Eastern European (CEE) jurisdictions. Although China is not a transitional state in a political sense, the transitional justice framework, particularly its analyses on how successor regimes in CEE countries deal with the aftermath of economic restructuring and societal reparations through the justice system, is of relevance to China’s ongoing judicial reforms and its future development. By comparing the judicial situation in China to that of CEE countries during transitional times, this Article attempts to analyze China’s distinctive judicial response to her massive economic and societal transformation so as to conceptualize “responsive justice” in China during transitional times.
Keywords: China; transitional justice; judges; judicial; transition; adjudicatory; mediatory; mediation; adjudication; process; justice system; systemic; reparations; responsive justice